2008
DOI: 10.1128/aac.00276-08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aspergillus fumigatus Burden in Pulmonary Tissue of Guinea Pigs by Quantitative PCR, Galactomannan Enzyme Immunoassay, and Quantitative Culture

Abstract: Early diagnosis of invasive pulmonary aspergillosis is problematic in some patient groups due to the lack of rapid, sensitive, specific, and reliable diagnostic tests. Fungal burden and therapeutic efficacy were assessed by survival, quantitative culture (CFU counts), galactomannan enzyme immunoassay (GM-EIA), and quantitative PCR (qPCR) in a new guinea pig model of invasive pulmonary aspergillosis using an aerosol challenge. At 1 day postinfection, qPCR determined that the pulmonary fungal burden was 2 log 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 31 publications
11
70
1
Order By: Relevance
“…]; Mead Johnson, Princeton, NJ) and cortisone acetate (250 mg/kg subcutaneously; Sigma, St. Louis, MO). Additional doses of cyclophosphamide (200 mg/kg) and cortisone acetate (250 mg/kg) were administered on day 3 postinoculation (18). Ceftazidime (100 mg/kg subcutaneously) was administered daily for prevention of bacterial infections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…]; Mead Johnson, Princeton, NJ) and cortisone acetate (250 mg/kg subcutaneously; Sigma, St. Louis, MO). Additional doses of cyclophosphamide (200 mg/kg) and cortisone acetate (250 mg/kg) were administered on day 3 postinoculation (18). Ceftazidime (100 mg/kg subcutaneously) was administered daily for prevention of bacterial infections.…”
Section: Methodsmentioning
confidence: 99%
“…Ceftazidime (100 mg/kg subcutaneously) was administered daily for prevention of bacterial infections. Guinea pigs were exposed to A. fumigatus 293 conidia at 1 ϫ 10 8 conidia/ml for 1 h in an aerosol chamber (18,19). In the antifungal treatment, experiment guinea pigs were divided to receive one of five regimens beginning at 1 day postinoculation (n ϭ 8 per group): (i) control, (ii) posaconazole at 10 mg/kg orally (p.o.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides quantification of fungal genomic DNA by qPCR, determination of cell wall compounds by chitin assays, CFU determinations, or evaluation of the tissue burden from histopathologic analyses are common. 9 All assays have in common that fungal burden can only be determined from sacrificed animals.…”
Section: -7mentioning
confidence: 99%
“…BAL fluid has been investigated thoroughly, since it was reported that detection of GM in BAL fluid increased the diagnostic sensitivity from 47% in serum to 85% [66], a comparison of 33 cases found that all 33 BAL specimens, but only nine serum specimens, were positive [67] and that BAL fluid from an established guinea pig model of IA gave a positive result more than 2 days sooner with BAL fluid than with serum [68]. This approach has been investigated for early diagnosis of IA following hematopoietic stem cell transplants [69], after solid organ transplantation [70], in patients with hematological malignancies and pulmonary infiltrates [71], chronic pulmonary disease [72][73][74] as well as in intensive care units [75] and in nonimmunocompromised patients [76].…”
Section: Antibody-targeted Biomarkersmentioning
confidence: 99%